Phalarodon Merriam 1910 - Roberts, Aubrey Jane; Engelschiøn, Victoria Sjøholt; Hurum, Jørn Harald (Zenodo, 2022)
Genus Phalarodon Merriam, 1910 Type species : Phalaodon fraasi Merriam, 1910; West Humbolt Range, Nevada, USA; Middle Triassic. Diagnosis .—Modified from Ji et al. (2015) and discussed in Økland et al. (2018). Premaxilla forms the anterior margin of external naris (also present in Mixosaurus panxianensis Jiang, Schmitz, Hao, and Sun, 2006); nasal region with a pronounced narial shelf; maxillary tooth implantation with sockets, dental groove absent posteriorly (completely absent in Phalarodon fraasi ); significant heterodonty between anterior and posterior teeth in the maxilla (not extreme in Phalarodon atavus ); teeth with laterally compressed horizontal section (circular in Phalarodon callawayi ); posterior tooth crown flat (conical in P. atavus ). Published as part of Roberts, Aubrey Jane, Engelschiøn, Victoria Sjøholt & Hurum, Jørn Harald, 2022, First three-dimensional skull of the Middle Triassic mixosaurid ichthyosaur Phalarodon fraasi from Svalbard, Norway, pp. 51-62 in Acta Palaeontologica Polonica 67 (1) on page 54, DOI:10.4202/app.00915.2021, http://zenodo.org/record/10981077